EFEKTIVITAS PENGGUNAAN APLIKASI INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN SISWA TERHADAP KONSEP ALJABAR - Ismail, Muhamad; Sari, Nella; Mahmudiyah, Rifa’atul; Yuliana S., Selfi; Rasilah, Rasilah (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This research aims to evaluate the effectiveness of using interactive applications in enhancing students' understanding of algebra concepts. Using a literature review method, this study collects and analyzes the results of various research conducted from 2019 to 2024. The literature reviewed includes both international and Indonesian studies that examine the use of interactive applications in algebra education. The results of the literature review indicate that interactive applications can significantly improve student understanding. Students using interactive applications show increased engagement, motivation, and learning outcomes compared to conventional teaching methods. Studies in Indonesia support these findings, reporting improved understanding and interest in algebra among students. These findings suggest that integrating technology into math education can be an effective strategy for enhancing student learning outcomes. Therefore, it is recommended that schools and educators consider using interactive applications as a teaching aid in algebra education.